2022
DOI: 10.3389/fgene.2022.933022
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Powdery Mildew Responsive Long Non-Coding RNAs in Cucurbita pepo

Abstract: Cucurbita pepo L. is an essential economic vegetable crop worldwide, and its production is severely affected by powdery mildew (PM). However, our understanding of the molecular mechanism of PM resistance in C. pepo is very limited. Long non-coding RNAs (lncRNAs) play an important role in regulating plant responses to biotic stress. Here, we systematically identified 2,363 reliably expressed lncRNAs from the leaves of PM-susceptible (PS) and PM-resistant (PR) C. pepo. The C. pepo lncRNAs are shorter in length a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…RNA-DNA hybrid (R-loop)-associated long non-coding RNAs (lncRNAs), e.g., AUXIN-REGULATED PROMOTER LOOP (APOLO), is found to be involved in DNA methylation and epigenetic control in Arabidopsis [30]. A genome-wide analysis of lncRNA in Camellia sinensis in response to nitrogen stress revealed a total of 16,452 lncRNAs, out of which 9451 were differentially expressed [31]. The detailed functional variability of lncRNA in plants includes growth and development, flowering and vernalization, light response, seed formation, yield, and stress response [32] (Table 1).…”
Section: Long Non-coding Rnas (Lncrna)mentioning
confidence: 99%
“…RNA-DNA hybrid (R-loop)-associated long non-coding RNAs (lncRNAs), e.g., AUXIN-REGULATED PROMOTER LOOP (APOLO), is found to be involved in DNA methylation and epigenetic control in Arabidopsis [30]. A genome-wide analysis of lncRNA in Camellia sinensis in response to nitrogen stress revealed a total of 16,452 lncRNAs, out of which 9451 were differentially expressed [31]. The detailed functional variability of lncRNA in plants includes growth and development, flowering and vernalization, light response, seed formation, yield, and stress response [32] (Table 1).…”
Section: Long Non-coding Rnas (Lncrna)mentioning
confidence: 99%
“…Recent studies have revealed the potential importance of lncRNAs as modulators of the development (22, 23) or the response to biotic (2426) or abiotic (27, 28) stress conditions in diverse Cucurbitaceae family members. However, detailed information about lncRNAs in cucurbits is limited, and only a list of unclassified and barely characterized lncRNAs in cucumber, melon and watermelon are currently available in GreeNC (29), PLncDB V2.0 (30) or CANTATAdb 2.0 (31), the most relevant databases containing plant lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Most plant lncRNAs have specific secondary structures and spatiotemporal expression patterns, and their regulatory mechanisms are complex and diverse [ 28 ]. With the continuous updating of new sequencing technologies and biological prediction algorithms, the action trace of lncRNA has been found in many links between plant growth [ 29 , 30 , 31 , 32 , 33 ] and stress response [ 25 , 34 ]. The authenticity identification and annotation of these lncRNAs have been enormously challenging, and there is still a long way to go for further experimental verification and validation.…”
Section: Introductionmentioning
confidence: 99%